Implementasi Sentimen Analysis Pengolahan Kata Berbasis Algoritma Map Reduce Menggunakan Hadoop - Fawaid Badri (Systemic: Information System and Informatics Journal, 2018)
Sentiment analysis is a field of text and information based research. Text documents in this language come from the web about socialization issues. The method used in this study uses algorithmic maps to calculate from a word that will be used to find a meaning in the context of public opinion. The map algorithm reduces the retrieval of data sets and converts them into a data set, data collection of individuals separated into tuples. The stages of the map algorithm reduce reading input data in the form of text stored in HDFS (Hadoop Distributed File System) then it will be processed according to the key and the value has been changed into tuple form. The next step is to process the shuffel and reduce it which will then produce a process from the data set that is processed. Furthermore, the research data uses sentiment analysis by using a map algorithm to reduce the amount of data that is very good